The Enduring Elegance of Thai Architecture: a Timeless Tradition in a Modern Context a Study of the Jim Thompson House as a Vernacular Example - Oroza, Lara Michaela Saskia Ricaldi (Institute for Research and Community Services Udayana University, 2025)
Thailand’s traditional architecture embodies a harmonious interplay between cultural identity, environmental adaptability, and spiritual beliefs. Its preservation was largely facilitated by the country’s unique status as Southeast Asia’s only nation to avoid colonization. This study examines the Jim Thompson House as a case study to explore vernacular Thai design, historical development, and challenges posed by modernization. With its steep roofs, stilted designs, and intricate craftsmanship, the house is celebrated as a masterpiece of traditional Thai architecture. However, questions arise regarding its authenticity as a representation of everyday Thai housing. This research also delves into the sociocultural and economic transformations that have contributed to the decline of traditional housing forms in modern Thailand. Findings reveal how the principles of vernacular Thai design can inform sustainable and culturally resonant architectural practices for contemporary challenges such as urbanization and climate change. Ultimately, this research argues that rather than viewing tradition and modernity as opposing forces, they can coexist, offering pathways to a more culturally enriched and sustainable architectural future. The Jim Thompson House serves not only as a historical artifact but as a source of enduring lessons for innovative design solutions today.